Penggunaan Citra DEMNAS untuk Desain Pola Tanam Alley Cropping pada Lahan Garapan Anggota KPPH Talang Mulya Kabupaten Pesawaran Provinsi Lampung - Trio Santoso; Machya Kartika Tsani; Surnayati Surnayati; Melya Riniarti (Fakultas Kehutanan Universitas Mulawarman, 2021)
Talang Mulya KPPH farmers has been applying agroforestry system for their land cultivation, but the cropping pattern applied has not been adapted to its sloping conditions and plant spacing which result on non-optimal yields produce. Alley Cropping pattern consider as the most suitable approach. Current analysis can be carried out using mapping techniques and remote sensing using digital elevation data imagery. The DEMNAS imagery was used in this study, results showed that the mean altitude reached 396.67 masl and land slope reached 20.92% in average. The design of the cropping pattern using 1 meter height intervals shows the results of the number of planting arrays of 31.96 strips with 3,564.96 meters in length which is higher than the land with a height interval of 2 meters which results in a total of 10.6 strips with and 942.97 meter lengths. However, the field of agricultural cultivation that can be formed on land with 1 meter height intervals only reaches 4.94 meters, while at 2 meters height intervals it can reach 16.03 meters.